The Myth of Sarvodaya : A Study of Vinoba's Concept - Tilak, Shrinivas (Brill | Manohar Publishers & Distributors, 2024)
This book is a revised master's thesis submitted to Concordia University, which is a reprint of the 1984 edition. Divided into six chapters, this book addresses the issue of Sarvodaya raised by a prominent Indian freedom fighter, educator, activist, and the successor of Mahatma Gandhi, Vinoba Bhave. This publication reminds me of Bhave as a successful reformer. This book offers a critical study of Bhave's effort to bring about revolutionary changes in traditional property, polity, and family relations and thereby, establish economic equality and social justice in modern India. For this purpose, it is argued here, that Vinoba made extensive use of the familiar Hindu myths and metaphors. The present study, therefore, also evaluates his relative success as a mythmaker and a transmitter of his cherished ideals and concepts through the medium of myths to his intended audiences.